2017
DOI: 10.1039/c7fo00227k
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization and bioactivities of polysaccharides from Pleurotus ferulae

Abstract: Pleurotus ferulae is an edible mushroom and has been used in Uygur medicine for a long time. In this study, we purified polysaccharides from P. ferulae (PFPS) and investigated its structural characteristics. We obtained a homogeneous PFPS with a molecular weight of around 1600 kDa and prominent characteristic polysaccharide groups, which mainly contained glucose (97%), followed by mannose and galactose (3%). Both H andC NMR spectra indicated that PFPS contained both α- and β-anomeric configurations. Atomic for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…The monosaccharide composition of PEP was analyzed according to the literature [43]. To analyze the monosaccharide composition, PEP was hydrolyzed with 4 M trifluoroacetic acid at 120 • C for 8 h. The hydrolyzed products of PEPs were derived with PMP according to the previous description [44].…”
Section: Preparation Of Polysaccharidesmentioning
confidence: 99%
“…The monosaccharide composition of PEP was analyzed according to the literature [43]. To analyze the monosaccharide composition, PEP was hydrolyzed with 4 M trifluoroacetic acid at 120 • C for 8 h. The hydrolyzed products of PEPs were derived with PMP according to the previous description [44].…”
Section: Preparation Of Polysaccharidesmentioning
confidence: 99%
“…GUPS-C was further purified by DEAE-52 chromatography according to our previous protocol with a minor modification [11]. In brief, 0.5 g of GUPS-C was dissolved in 200 mL distilled water and filtered through 0.22 µM filter.…”
Section: Purification Of Gupsmentioning
confidence: 99%
“…Many plant-derived polysaccharides have been extensively studied for immune enhancing effect because of their safety profiles [9]. Polysaccharides can activate macrophages, dendritic cells (DCs), T lymphocytes, B lymphocytes, and natural killer cells to produce immune-related molecules, such as cytokines, antibodies, and complement molecules [10][11][12]. Recently, several studies have shown that polysaccharides bind to receptors such as Toll-like receptors (TLRs) on the surface of macrophages or DCs to trigger several down-stream signaling pathways to promote immune responses [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The monosaccharide composition was determined by HPLC according to our previous report with some modification (J. Li et al, 2017). Briefly, TAPS and OSPS were hydrolysed with 4 M trifluoroacetic acid at 120°C for 2 h, and the fractions were incubated with 1phenyl-3-methyl-5-pyrazolone (PMP, ALADDIN, Shanghai) at 70°C for 60 min.…”
Section: Determination Of Monosaccharide Compositionmentioning
confidence: 99%
“…However, the activity of PFPS might be correlated with its triple-helix conformation (J. Li et al, 2017), which conferred higher immunostimulating activity (Falch et al, 2000).…”
Section: The Immunoregulatory Effects Of These Four Polysaccharides Omentioning
confidence: 99%